2009
DOI: 10.1177/0093650208326464
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Media Synchronicity and Task Performance

Abstract: The study examines effects of media synchronicity in a group problem-solving task. The media characteristics of parallelism, immediacy of feedback, and reprocessability are varied within text-based computer-mediated communication. The hidden profile task requires groups to exchange unshared pieces of information and to integrate them. Contrary to expectations, asynchronous media characteristics do not support the production of unshared information. Furthermore, asynchronous media characteristics result in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…These studies are supported by media synchronicity theory that suggests that symbol variety (the ability to provide information in various formats, e.g. verbal, non-verbal) helps to underpin effective communication (M€ unzer & Holmer, 2009).…”
Section: Factor 4 Formmentioning
confidence: 92%
See 2 more Smart Citations
“…These studies are supported by media synchronicity theory that suggests that symbol variety (the ability to provide information in various formats, e.g. verbal, non-verbal) helps to underpin effective communication (M€ unzer & Holmer, 2009).…”
Section: Factor 4 Formmentioning
confidence: 92%
“…Written communication also provides a record of the interaction that can encourage learner reflection through user 'reprocessability' (i.e. examination and later processing) (M€ unzer & Holmer, 2009) and annotation inclusion (Bridge & Appleyard, 2005). In addition, written text can be delivered without breaking the professional flow of an activity, encouraging later reflection (Barton & Wolery, 2007).…”
Section: Factor 4 Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Channel expansion theory similarly states that experience with the electronic medium, experience with the messaging topic, experience with the organisational context, and experience with communication partners will overtime help in developing associated social information-processing schema bases that help in effectively encoding and decoding messages (Carlson and Zmud, 1999). Evidence of this was found in a more recent study by Munzer and Holmer (2009) where they found that people engaging in asynchronous CMC compensated for the decrease in coherence of the discussion by showing higher engagement in integrating information during discussion. Kock (1998Kock ( , 2001 in his compensatory adaptation model goes one step further to state that communication through electronic media gives rise to more elaborate and better quality contributions when compared to FTF communication in the process of compensating for the limitations of the electronic medium.…”
Section: Interfirm Internet Driven Communication: From a Cmc Perspectivementioning
confidence: 97%
“…A competing hypothesis is suggested by some findings that virtual teams may exercise more vigilance than do face-to-face teams. Specifically, Münzer and Holmer (2009) and Münzer and Borg (2008) found evidence for a compensatory model wherein virtual teams spontaneously increase vigilant behaviors (such as repetitions of information) in an effort to make up for the challenges of asynchronous computer-mediated communication. Their findings are consistent with past research on face-to-face teams that attention to interaction process may increase as a group’s task structure becomes more complex or intractable (Hirokawa, 1990; Poole & Roth, 1989).…”
Section: Vigilant Interaction Theorymentioning
confidence: 99%